2007
DOI: 10.1007/s11255-007-9258-y
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric nephrology patients are overweight: 20 years' experience in a single Canadian tertiary pediatric nephrology clinic

Abstract: The increased rate of obesity in our studied population suggests that pediatric nephrology patients are at even greater risk for developing CKD later in life than could be predicted from their renal disease only. We recommend therapeutic intervention to address this potentially modifiable risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Currently, the proportion of overweight and obese Norwegian TX children is twice that of the general Norwegian child population [52]. TX children are probably exposed to the same trends as the general population in terms of the obesity epidemic and a sedentary lifestyle [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the proportion of overweight and obese Norwegian TX children is twice that of the general Norwegian child population [52]. TX children are probably exposed to the same trends as the general population in terms of the obesity epidemic and a sedentary lifestyle [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Of particular concern, Filler et al [43] recently reported a significant increase in BMI z-score in their pediatric nephrology population over the last three decades, with an overall BMI z-score higher than the comparable USA young population in the same period. This puts young nephrology patients at even greater risk of developing CKD later in life than could be depicted from their renal disease only.…”
Section: Obesity-related Renal Injury In Childhoodmentioning
confidence: 99%
“…Hsu et al demonstrated the effect of body mass index (BMI) on the risk of end-stage renal disease in a cohort of 330,252 persons in California between 1964 and 1985, reporting a strong doseresponse relationship between the baseline BMI and the risk of chronic kidney disease (CKD) [2]. Filler et al demonstrated that pediatric renal patients had significantly higher BMI zscores than the normal population at a tertiary center in Canada over a period of 2 decades [3]. In children with renal transplants, kidney samples obtained from obese donors (BMI >30) had a lower glomerular filtration rate (GFR) and higher allograft dysfunction rate than kidney samples obtained from lean individuals (BMI <25) [4].…”
Section: Introductionmentioning
confidence: 99%